2020
DOI: 10.3389/fimmu.2020.00518
|View full text |Cite
|
Sign up to set email alerts
|

BTLA-Expressing Dendritic Cells in Patients With Tuberculosis Exhibit Reduced Production of IL-12/IFN-α and Increased Production of IL-4 and TGF-β, Favoring Th2 and Foxp3+ Treg Polarization

Abstract: Little is known about how tuberculosis (TB) impairs dendritic cell (DC) function and anti-TB immune responses. We previously showed that the B and T lymphocyte attenuator (BTLA), an immune inhibitory receptor, is involved in TB pathogenesis. Here, we examined whether BTLA expression in TB affects phenotypic and functional aspects of DCs. Active TB patients exhibited higher expression of BTLA in myeloid dendritic cells (mDCs) and plasmacytoid DCs (pDCs) subsets compared with healthy controls (HCs). BTLA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Jones et al discovered that BTLA + DCs governed the conversion of peripheral Treg cells by upregulating CD5, thus enhancing the tolerance of peripheral Treg cells ( 41 ). Moreover, active pulmonary tuberculosis drives BTLA expression in DCs, thereby inhibiting Th17 and Th22 responses induced by DCs and promoting Treg and Th2 differentiation ( 42 ). Further, urothelial cancer induces the overexpression of BTLA in DCs, resulting in reduced secretion of effector cytokines ( 43 ).…”
Section: Btla Effects In Immunocytesmentioning
confidence: 99%
“…Jones et al discovered that BTLA + DCs governed the conversion of peripheral Treg cells by upregulating CD5, thus enhancing the tolerance of peripheral Treg cells ( 41 ). Moreover, active pulmonary tuberculosis drives BTLA expression in DCs, thereby inhibiting Th17 and Th22 responses induced by DCs and promoting Treg and Th2 differentiation ( 42 ). Further, urothelial cancer induces the overexpression of BTLA in DCs, resulting in reduced secretion of effector cytokines ( 43 ).…”
Section: Btla Effects In Immunocytesmentioning
confidence: 99%
“…Zhang et al. reported that BTLA + DCs promoted Treg and Th2 polarization of T cells in human lung tuberculosis ( 23 ). Altogether, these data highlight the importance of BTLA in immune homeostasis.…”
Section: Btla and Hvem Implication In Immune Homeostasismentioning
confidence: 99%
“…Upon differentiation, moDCs undergo an activation process that, depending on their membrane receptors and secreted cytokines, means that moDCs may have either a pro-inflammatory or tolerogenic function. Pro-inflammatory activation is with CD80 and CD86 surface marker expression and IL-12p70 cytokine secretion, whereas PD-L1 and PD-L2 surface marker expression and IL-10 cytokine secretion are considered to prompt tolerogenic or anti-inflammatory activation of moDCs [ 6 ]. Any microenvironmental disturbance produces dysfunctional mDCs that may initiate inflammatory or autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%